Multi Methods of Teaching the Lord Jesus: A Strategy to Shape the Scientific Attitude of Students - Elieser R Marampa; Gideon Widiono; Korina Sanosa (International Perspectives in Christian Education and Philosophy, 2024)
Scientific attitude is a very important attitude to be possessed by every student in following the learning process. Therefore, this study aims to examine the teaching method of the Lord Jesus as a strategy in shaping the scientific attitude of students. Through a qualitative approach with literature review techniques, the author examines in depth the method of teaching Jesus as a strategy in shaping the scientific attitudes of students. The results of this study found that to shape the scientific attitude of students, it is necessary to be guided by the teaching methods of the Lord Jesus, such as discovery and inquary methods, discussion methods, problem-based, and storytelling methods. Therefore, teachers of Christian religious education are required to always emulate the Lord Jesus and think creatively in shaping the scientific attitude of students in accordance with teaching conditions in the 21st century.